Complex primary and revision total knee arthroplasty : A clinical casebook - Springer, Bryan D.; Curtin, Brian M. (Springer International Publishing, 2015)
Comprised exclusively of clinical cases covering complex primary and revision total knee arthroplasty, this concise, practical casebook will provide orthopedic surgeons with the best real-world strategies to properly manage the more complicated forms of knee replacement they may encounter. Each chapter is a case that opens with a unique clinical presentation, followed by a description of the diagnosis, assessment and management techniques used to treat it, as well as the case outcome and clinical pearls and pitfalls. Cases included illustrate different management strategies for primary knee arthroplasty, including the varus and valgus knee, flexion contracture and extra-articular deformity, as well as periprosthetic infection and revision total knee arthroplasty, including deficient extensor mechanism, periprosthetic femur fracture and ligamentous instability. Pragmatic and reader-friendly, Complex Primary and Revision Total Knee Arthroplasty: A Clinical Casebook will be an excellent resource for orthopedic surgeons confronted with a challenging knee joint replacement.